PENGGUNAAN LEMBAR KERJA MAHASISWA SEBAGAI MEDIA PEMBELAJARAN MATA KULIAH METODE NUMERIK - Ni Kadek Rini Purwati (Emasains : Jurnal Edukasi Matematika dan Sains, 2016)
Collaborative learning is one model of learning that can be applied in the learning course of numerical methods. This learning is not only emphasizes the unity and the ability of the group, but also the ability of each individual to understand the material. To support this learning required an instructional media such as the student worksheets. Using student worksheets in learning of numerical methods aims to help students determine the range of material and translation of the material. This research is a descriptive research with quantitative approach that carried out on students majoring in mathematics education IKIP PGRI Bali in sixth semester. The sampling technique used was purposive sampling. Description is based on questionnaire data relating on using student worksheets. Based on the analysis, using student worksheet received good response from students and can assist students in learning. Based on the results of these studies are also expected some improvements and development on a worksheet in terms of both translation and writing materials